2022
DOI: 10.1109/jphot.2022.3199043
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional High-Efficiency Transceiver Integrated Optical Phased Array With Dual-Port Antenna

Abstract: We propose a 1 × 32 silicon photonics transceiver integrated optical phased array (OPA) with a large scanning angle. It can process receive and transmit signals simultaneously, which effectively increases the on-chip signal transmission efficiency. The simulation shows that the phase-tuned 62.2°lateral beam steering without grating lobe and the wavelength-tuned 31.2°longitudinal beam steering can be achieved in the transmitting mode, and the overall optical loss is less than 9.1 dB. In the receiving mode, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…OPAs can also function as receivers by detecting the emitting angle of an incoming beam [128], allowing for the creation of directional reflectors [129] and OPA cameras [130]. By combining the receiving and emitting capabilities of OPAs, optical transceivers can be developed [131][132][133], enabling wireless communication with directional links [77,[134][135][136][137][138] and also underwater wireless communication [139,140]. Additionally, OPAs have potential in bio-applications, where a neural stimulation OPA [141] and a neural probe [142] have been developed.…”
Section: Other Applicationsmentioning
confidence: 99%
“…OPAs can also function as receivers by detecting the emitting angle of an incoming beam [128], allowing for the creation of directional reflectors [129] and OPA cameras [130]. By combining the receiving and emitting capabilities of OPAs, optical transceivers can be developed [131][132][133], enabling wireless communication with directional links [77,[134][135][136][137][138] and also underwater wireless communication [139,140]. Additionally, OPAs have potential in bio-applications, where a neural stimulation OPA [141] and a neural probe [142] have been developed.…”
Section: Other Applicationsmentioning
confidence: 99%
“…However, studies have shown that the use of an OPA for signal reception can receive the incident optical signal directionally through phase control. It means that it can actively receive the optical signal in the specified direction and reject the signal in other directions [22]. This function is of great value in many applications.…”
Section: Introductionmentioning
confidence: 99%